Efektivitas Pemberian Trunk Exercise pada Plantar Flexor Ankle Exercise terhadap Kemampuan Berjalan Anak Cerebral Palsy Diplegi di Klinik Karya Husada - Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Siregar, Memo Martua Holong (Jurnal Riset Hesti Medan, 2024)
Objective: To determine the difference in effectiveness between trunk exercise with plantar flexor ankle exercise and plantar flexor ankle exercise on the walking ability of children with cerebral palsy diplegi. Method: An experimental study with a pre-post-test design. The total sample in this study were 10 people who were divided into 2 groups and each group numbered 5 people. Group I with plantar flexor ankle exercise intervention and group II with the addition of trunk exercise to plantar flexor ankle exercise. The value of walking ability is measured by 1-minute walk test. Results: Test hypotheses I and II with paired sample t-tests showed p values < 0.002 and p <0.001. This means that the provision of intervention groups I and II can significantly improve the ability to walk. Furthermore, hypothesis III between two groups with independent sample t-test obtained p value <0.004, meaning that there is a significant difference between group I and group II and this study shows that the addition of trunk exercise in plantar flexor ankle exercise is better than plantar flexor ankle exercise alone with differences in the average difference and standard deviation of 9.11 ± 2.75 in group I and 11.84 ± 2.05 in group II. Conclusion: there is a difference between plantar flexor ankle exercise and giving trunk exercise to plantar flexor ankle exercise can improve walking ability.